Digital Reading Engagement of Junior High School Students during the Online Learning - Risna Amalia Izati; Lies Amin Lestari; Slamet Setiawan (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
The pandemic of COVID-19 has forced the teachers and students to hold the teaching and learning remotely. All the process of learning was conducted online via various mobile applications. Students widely use smartphones as a medium to receive learning materials, join online classes, and study. However, it was questioned whether students are engaged with their reading materials when they have to read the texts on screen or digitally and learn from them. It is expected that the use of digital devices has influenced students' reading engagement, especially when the reading is to learn. This study aims to find out about the students' engagement in reading digital texts during online learning. The study collects the data from self-report questionnaires, interviews, and observation. The result shows that students do not experience behavioral and affective engagement as well as a negative response while they are reading the texts onscreen during online learning.